Development and design of a learning management system - Mok, Jelyn Pei Yu (Nanyang Technological University, 2022)
Learning Management Systems (LMS) are used by schools and independent instructors to engage their students into online learning. Though these LMSs can consists of a range of features that is functional and helps to create, deliver, and sell online courses, there are still some design or implementation flaws. These flaws cause results in poor user experience such as making the process of creating courses too time consuming for instructors and causing the courses to appear too overwhelming for students to be able to complete them.